The Effect of Firm Value, Financial Performance, Environmental Performance, and Firm Size on Carbon Disclosure - Rahmah, Nailur; Sidharta, Eka Ananta; Sudarto, Triadi Agung (Journal of Applied Business, Taxation and Economics Research, 2024)
The industrial sector is a leader in the global increase of carbon. As a result, the risk of natural disasters is inevitable. One way that can be done to reduce the occurrence of natural disasters is to reduce carbon emissions in the industrial sector. The purpose of this study was to determine the effect of company value, financial performance, environmental performance, and company size on carbon disclosure. The population used in the study amounts to 50 well-known companies listed on the European Stock Market. Based on the purposive sampling method, 16 companies were selected. The data for this study were sourced from the annual reports and sustainability reports of the companies. The study found that firm value and firm size have a positive effect on carbon disclosure. This is a signal for companies, in making efforts to reduce carbon emissions. The greater the efforts made by the company in reducing emissions, the higher the profitability achieved by the company.